PENGARUH MOTIVASI KERJA TERHADAP PRESTASI KERJA GURU SEKOLAH DASAR DENGAN KEPRIBADIAN SEBAGAI VARIABEL MODERASI - Nur Alam Romadhon (MNJ 11 UMY 420, 2011)

(untitled)
This research aim to analyzing the influence of work motivation to work achievement with personality as a moderating. Objects in this research are elementary schools in Region of Suryowijayan, SD Muhammadiyah Suryowijayan and SD Negeri Suryowijayan. Subjects are teachers of SD Muhammadiyah Suryowijayan and teachers of SD Negeri Suryowijayan. Data research obtained by enquettes spreading to 40 teachers consisted of 22 teachers of SD Muhammadiyah Suryowijayan and 18 teachers of SD Negeri Sury